Predicting infectivity: comparing four PCR‐based assays to detect culturable SARS‐CoV‐2 in clinical samples. Issue 2 (13th December 2021) - Bruce, Emily A; Mills, Margaret G; Sampoleo, Reigran; Perchetti, Garrett A; Huang, Meei‐Li; Despres, Hannah W; Schmidt, Madaline M; Roychoudhury, Pavitra; Shirley, David J; Jerome, Keith R; Greninger, Alexander L; Botten, Jason W
Abstract: With the COVID‐19 pandemic caused by SARS‐CoV‐2 now in its second year, there remains an urgent need for diagnostic testing that can identify infected individuals, particularly those who harbor infectious virus. Various RT–PCR strategies have been proposed to identify specific viral RNA species that may predict the presence of infectious virus, including detection of transcriptional intermediates (e.g., subgenomic RNA [sgRNA]) and replicative intermediates (e.g., negative‐strand RNA species). Using a novel primer/probe set for detection of subgenomic (sg)E transcripts, we successfully identified 100% of specimens containing culturable SARS‐CoV‐2 from a set of 126 clinical samples (total sgE CT values ranging from 12.3 to 37.5). This assay showed superior performance compared to a previously published sgRNA assay and to a negative‐strand RNA assay, both of which failed to detect target RNA in a subset of samples from which we isolated live virus. In addition, total levels of viral RNA (genome, negative‐strand, and sgE) detected with the WHO/Charité primer‐probe set correlated closely with levels of infectious virus. Specifically, infectious virus was not detected in samples with a CT above 31.0. Clinical samples with higher levels of viral RNA also displayed cytopathic effect (CPE) more quickly than those with lower levels of viral RNA. Finally, we found that the infectivity of SARS‐CoV‐2 samples is significantly dependent on the cell type used for viral isolation, as Vero E6 cells expressing TMRPSS2 extended the analytical sensitivity of isolation by more than 3 CT compared to parental Vero E6 cells and resulted in faster isolation. Our work shows that using a total viral RNA Ct cutoff of > 31 or specifically testing for sgRNA can serve as an effective rule‐out test for the presence of culturable virus. Synopsis: Four RT‐PCR based assays were tested on a panel of 126 SARS‐CoV‐2 RNA‐positive clinical samples to assess the ability of each to predict the presence of culturable infectious virus. The levels of SARS‐CoV‐2 viral RNA correlate closely with levels of infectious virus. The expression of TMPRSS2 makes Vero E6 cells significantly more sensitive to SARS‐CoV‐2, resulting in faster and more successful viral isolation. Infectious SARS‐CoV‐2 virus was not isolated from any sample with an E gene CT>31 (using the WHO/Charité primer probe set). A novel primer‐probe set ("Mills sgE") developed to specifically detect sgE was able to identify 100% of samples containing culturable SARS‐CoV‐2 virus. Negative‐strand RNA was detected in only a subset of samples with culturable SARS‐CoV‐2 and should not be used to rule out infectious virus in clinical specimens. Abstract : Four RT‐PCR based assays were tested on a panel of 126 SARS‐CoV‐2 RNA‐positive clinical samples to assess the ability of each to predict the presence of culturable infectious virus.